Metabolic functions of the Pseudomonas aeruginosa aminoglycoside resistance gene, aph - Aksoy, Cemile Selin (2024)
Various factors contribute to the pathogenicity of Pseudomonas aeruginosa, an opportunistic pathogen responsible for severe infections, particularly in immunocompromised individuals. Among these factors, multidrug resistance stands out as a significant concern. The aph gene, chromosomally encoded in P. aeruginosa, plays a pivotal role in conferring resistance to kanamycin, an aminoglycoside class antibiotic. A study on the aph gene, highlighted the effect of the carbon source 4-HPA on aph transcription, suggesting a link between kanamycin resistance and metabolic processes. This finding underlines the need to explore alternative metabolic pathways associated with the aph resistance gene. Understanding these associations could pave the way for the development of novel antimicrobial strategies targeting aph associated pathways in bacterial metabolism. Therefore, the current study aimed to uncover the metabolic associations of the aph antibiotic resistance gene within P. aeruginosa.